The coexistence of the internal jugular vein duplication with a contralateral internal jugular drainage of the external jugular vein - George Triantafyllou; Katerina Vassiou; Marianna Vlychou; George Tsakotos; Răzvan Costin Tudose; Mugurel Constantin Rusu; Maria Piagkou (Elsevier, 2024)
Introduction: The current imaging report describes a unique coexistence of the neck venous system morphological variants. Methods: The imaging study of a 75-year-old male patient was isolated due to its unique venous system. Results: An internal jugular vein (IJV) duplication (main-typical and accessory IJVs) was identified on the right side, coexisting with a facial vein (FV) drainage into the accessory IJV. On the left side, the external jugular vein (EJV) was draining into the IJV and the FV into the EJV. A transverse anastomosis of the EJV and anterior jugular vein (AJV) was identified. Conclusions: The IJV duplication is a rare morphological variant, and its coexistence with other co-variants complicates the area's anatomy. Understanding these morphological variants is crucial for anesthesiologists and surgeons, as it can help prevent iatrogenic injury.